Profile of Cognitive Barriers of Students in the Transition from Arithmetic to Algebra in Learning Algebraic Form - Dwi Roudhotillah; Fadhila Rizqia Dewi Putri; Baiduri Baiduri; Mayang Dintarini; Rabia Rasheed (Journal of Teaching and Learning Mathematics, 2026)
This study aims to analyze the cognitive barriers experienced by seventh-grade students in solving algebraic problems in a public junior high school in Malang Regency. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of three seventh-grade students who were selected purposively based on indications of cognitive barriers in learning algebra. Data were collected through written tests on algebraic problems and in-depth interviews. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that students experienced four forms of cognitive barriers, namely: (1) lack of conceptual understanding, especially in distinguishing like terms and performing algebraic operations; (2) reasoning errors in formulating solution steps and interpreting algebraic problems; (3) use of inappropriate cognitive strategies, such as converting variables into numbers so they can be calculated; and (4) mental attitudes that do not support the learning process, such as low self-confidence, lack of thoroughness, and a tendency to rush in solving problems. These findings indicate that students still experience difficulties in making the transition from arithmetic to algebraic thinking. The implications of this research emphasize the importance of implementing learning strategies that emphasize conceptual understanding, the development of mathematical reasoning, the use of meaningful algebraic representations, and strengthening students' positive attitudes towards mathematics to minimize the emergence of cognitive barriers in algebra learning.